(untitled) (Revista de Letras Norte@mentos, 2016)
This article is a result of our English teaching practice in a Children Education State Center, which belongs to a State University in the north of Paraná. The study was conducted with five-year-old students who had English lessons with pre-service teachers from the same University. The overall objective of the research was to investigate the importance of mastering the textual genre "game rules" – in our case, a board game – to carry out the developed and implemented activities during classes. This research, of qualitative nature, is based on the action research methodology (SAGOR, 2000; LEWIN, 1948). The data was composed of reflective diaries written by pre-service teachers during the mandatory internship, main locus of our research. The results showed that knowing the textual genre enabled students effective engagement in the discursive event proposed, thus achieving the main objective of the activity: recalling contents from the previous semester. In addition to that, we realized that the fact that the students had been exposed to such textual genre enabled a more meaningful English learning.